TEORI DAN PERBANDINGAN MANAJEMEN MUTU BARAT DAN ISLAM: TEORI DAN PERBANDINGAN MANAJEMEN MUTU BARAT DAN ISLAM - Mila Kamalasari; Baiq Nadia Zulva; M. Sobry (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality management is a crucial component of modern organizational practice that emphasizes continuous improvement, customer satisfaction, and operational efficiency. In the Western perspective, quality management theory has evolved through rational and empirical approaches focused on measurable outcomes and process optimization. Scholars such as W. Edwards Deming, Joseph Juran, and Philip Crosby established foundational principles of quality management, including process control, continuous improvement, and employee involvement across all organizational levels.In contrast, the Islamic perspective on quality management extends beyond efficiency and technical quality, integrating spiritual and ethical dimensions derived from the Qur’an and Hadith. Core values such as ihsan (excellence in work), amanah (trustworthiness), and maslahah (public benefit) form the basis for a value-oriented and justice-driven quality system. This study aims to compare Western and Islamic theories of quality management by examining their philosophical foundations, core principles, and practical applications. The findings indicate that while both frameworks pursue superior quality, the Islamic approach emphasizes harmony between material and spiritual aspects, whereas the Western model predominantly focuses on rational, systematic, and technical dimensions of management.